2022
DOI: 10.1088/1361-6668/ac4ba0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and densification mechanism of powder-in-tube Ba x K1−x Fe2As2 superconductors

Abstract: BaxK1-xFe2As2 (BaK-122) iron-based superconductors (IBSs) have been considered to be promising for high-field applications. The transport J c performance of BaK-122 wires and tapes is continuously enhanced by introducing advanced fabricating methods. The mass density of BaK-122 superconducting core in wires and tapes is important to the transport J c performance and related to the mechanical behavior during preparation. In this work, the mechanical property parameters includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The hardness values of the tape fabricated using the pre-annealing method by Li et al [32] reaches 112.70, which is also lower than that of the pre-composite tape. Previous study has concluded that hardness and density are positively correlated in Ba-122 polycrystalline superconducting materials [28]. The increase in hardness of the pre-composite tape indicates the increase in density, which promotes the improvement of transport performance.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The hardness values of the tape fabricated using the pre-annealing method by Li et al [32] reaches 112.70, which is also lower than that of the pre-composite tape. Previous study has concluded that hardness and density are positively correlated in Ba-122 polycrystalline superconducting materials [28]. The increase in hardness of the pre-composite tape indicates the increase in density, which promotes the improvement of transport performance.…”
Section: Resultsmentioning
confidence: 87%
“…The increase in hardness of the pre-composite tape indicates the increase in density, which promotes the improvement of transport performance. The hardness of Ba-122 tape is highly dependent on the characteristic of the sheath material, and generally the greater the thickness and mechanical strength of the sheath, the greater the increase in hardness for the superconducting core [28]. The pre-composite method is equivalent to making the initial thickness of the sheath higher, which helps to improve the strength of the mechanical process and leads to an increase in the density of the superconducting core to some extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 According to the research on the relationship between the Vickers hardness and mass density, a hardness value of 200 corresponds to about 90% theoretical density of the Ba-122 sample. 50 In this work, hardness tests were conducted for the local areas in the superconducting filaments on the well-polished transverse section of the Ba-122 tape-in-tube wires. The obtained hardness data are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%